Ispol'zovanie iskusstvennogo srednegor'ya pri podgotovke k sorevnovaniyam po lyzhnym gonkam - Martynov, V. S.; Grushin, A. A.; Kostina, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The authors represent the results of their research to reveal the efficiency of the artificial middle mountain conditions` employment for the sky racers` training when preparing for competitions. The special apartments equipped to create the conditions of artificial middle mountain up to the 5000 m above sea level had been used in the regime of 3000 m.